Ict Skills for Professional Development teaching in Basic Education - Hernández Suárez, César Augusto; Arévalo Duarte, Mayra Alejandra; Gamboa Suárez, Audin Aloiso (Universidad Pedagógica y Tecnológica de Colombia, 2016)
This article shows the results of further research in educational institutions in the city of Cucuta on ICT skills and their integration into teaching practice. The purpose of this advance was to identify and relate the levels of ICT skills reporting teachers of Basic, considering their profile training and reference to the proposed by the Ministry of National Education (MEN) of Colombia in 2013 model. It is a descriptive correlational quantitative research approach in which the levels of ICT skills MEN model from the dimensions of expertise in the teachers are measured. 255 teachers from 16 educational institutions, which answered a Likert scale were selected. Globally, the results show that teachers show a good level of ICT skills. The self-reported skills in different dimensions, on the other hand, show high and significant correlations with each other, which shows that it is a consolidated knowledge and that there is a partial integration of ICT in the classroom.